Transformational governance : how boards achieve extraordinary change - Gazley, Beth, 1961-; Kissman, Katha (ASAE, The Center for Association Leadership : John Wiley & Sons, 2015)
"There has never been so much pressure on nonprofit boards of directors to achieve a level of accountability that meets public and stakeholder expectations. Member-serving association boards maybe especially challenged by their more complex affiliate structures and a greater emphasis on representative governance. But what does the journey to good governance look like? Markedly different from existing board development books, this modern approach focuses lesson the behaviors and qualities of "high-performing boards" and more on the stages and processes that directors and their staff used to transform their boards. Based on research funded by the ASAEFoundation, the book fills a gap in the governance literature by emphasizing diagnosis and problem solving, using the actual tools and activities implemented by 85 transformed associations. Combining the credibility of scholarly research with lively and compelling stories, tools, and teachable moments, this book is designed to help associations and other nonprofit organizations achieve the entire journey to good governance, from first to laststeps"--